Ketertindasan dan Perlawanan Perempuan Interseksionalitas dalam Cerpen “Pohon Api” Karya Oka Rusmini - Mustaqim, Andika Hendra (UI Scholars Hub, 2018)
The main objective of this research is mapping and exploring how the oppression and resistance of the main character (Kekayi) in Oka Rusmini’s short story Pohon Api are manifested through the strategic use of her own intellectuality, not only her beauty; her focus on future visions; and her attempt to garner support from the higher authority to win the competition. This research applied the qualitative approach with content analysis method. This research reveals that Kekayi, the main character in Oka Rusmini’s short story